The Teacher Efforts In Improving The Students Reading Ability Of MA Hamzanwadi AT Pancor - Rizal, Syamsul; Jayadi, Sudarman (Fikroh: (Jurnal Studi Islam), 2024)
Abstract Dormitory or boarding school education is non-formal education in Islamic boarding schools. Where the dormitory is managed by a caretaker who has a very important role in teaching the yellow book which is the hallmark of Islamic boarding schools. The yellow book itself is a classic book written in Arabic without harokat, making the yellow book a fairly high level of difficulty to study. So caregivers must try so that students can read and understand the Yellow Book properly and correctly. This research aims to determine caregivers' efforts to improve students' ability to read the Yellow Book, supporting factors and obstacles experienced by caregivers. The type and approach of this research is descriptive qualitative research. Researchers obtained data through observation, interviews and documentation, the data analysis techniques used were collecting, reducing and displaying data, testing the validity of the data using triangulation. The results of the research conducted by the researchers concluded that: the caregivers reviewed the efforts made by previous caregivers, listened to the students' reading books and then put the students into certain classes based on their understanding of the books. The caregiver determines the method used to teach the yellow book. The supporting factors are books and scriptures, students' interest and enthusiasm for learning and competent teachers in the field of yellow books. The challenges for caregivers are the lack of caregivers who teach the yellow book and the fluctuating morale of the students as well as the caregivers' status as students.